Firm's Absorptive Capacity: The Case of Vietnamese Manufacturing Firms - Duong Vu Hoang (Review of Economic Perspectives, 2018)
Absorptive capacity is an essential factor for the development of any firm. Hence, numerous researchers use it when proposing different approaches and measurements. However, due to the ambiguity of definition of absorptive capacity, some studies focused on the within-firm aspects of absorptive capacity while some looked at the inter-firm aspects. Consequently, there are several proxies for absorptive capacity, which are unlikely to reach an agreement. Therefore, this study aims for the simplified measurement by defining the absorptive capacity of a firm as the gap in persistent efficiency between the firm and the best foreign firm in the same industry. The persistent efficiency of a firm is estimated by using single stage maximum likelihood method. This measurement is applied to the case of Vietnamese manufacturing firms from 2007 to 2015 to estimate the domestic absorptive capacity. The results show that domestic firms in the manufacture of tobacco products sub-sector have the best absorptive capacity and the manufacture of beverages sub-sector have the worst one. Finally, the validity of the proxy is confirmed when the study finds the positive correlation between absorptive capacity and a firm's age, size, technology level and skills of its workers.
Keywords: 330; Absorptive capacity; Persistent efficiency; Vietnamese manufacturing firms